Private Information in Sequential Common-Value Auctions - Johannes Hörner; Julian Jamison (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2006)
We study an in.nitely-repeated .rst-price auction with common values. Initially, bid-ders receive independent private signals about the objects. value, which itself does not change over time. Learning occurs only through observation of the bids. Under one-sided incomplete information, this information is eventually revealed and the seller extracts es-sentially the entire rent (for large discount factors). Both players.payoþs tend to zero as the discount factor tends to one. However, the uninformed bidder does relatively better than the informed bidder. We discuss the case of two-sided incomplete information, and argue that, under a Markovian re.nement, the outcome is pooling: information is revealed only insofar as it does not aþect prices. Bidders submit a common, low bid in the tradition of .collusion without conspiracy.
Keywords: C72; D44; 330; repeated game with incomplete information; private information; ratchet effect; first-price auction; dynamic auctions; Auktionstheorie; Asymmetrische Information; Wiederholte Spiele; Theorie